Evaluation of Gravitational Insecurity in School-Age Children Diagnosed with Learning Disorder (International Journal of Scientific Research and Management (IJSRM), 2022)
AIM: This study was conducted to determine the incidence of Gravitational Insecurity in individuals with Specific Learning Disorder. MATERIAL AND METHODS: We included 99 children, 65 boys and 34 girls, diagnosed with Specific Learning Disorder in our study. All children participating in the study were attending a special education and rehabilitation center. Physically independent individuals without any orthopedic or neurological diagnosis other than Specific Learning Disorder were included in the study. 99 children were evaluated with the Gravitational Insecurity Assessment and the data obtained were statistically analyzed. RESULTS: Gravitational Insecurity is commonly seen in individuals diagnosed with Specific Learning Disorder. In individuals diagnosed with Specific Learning Disorder, the severity and incidence of Gravitational Insecurity increase with age, there is no significant difference between genders, and these individuals react to different movement patterns at different levels. In individuals diagnosed with Specific Learning Disorder with Gravitational Insecurity, postural symptoms of Gravity Insecurity are observed at higher rates than emotional symptoms. The incidence of both postural and emotional symptoms increases with age.